Three-stage gaseous biofuel production combining dark hydrogen, photo hydrogen, and methane fermentation using wet Arthrospira platensis cultivated under high CO2 and sodium stress. (15th September 2017) - Ding, Lingkan; Cheng, Jun; Lu, Hongxiang; Yue, Liangchen; Zhou, Junhu; Cen, Kefa
Highlights: An integrated process from cyanobacterium cultivation to utilization was conducted. High CO2 and NaCl stress boosted carbohydrate accumulation in Arthrospira platensis. Total carbohydrates in A. platensis occupied 53.4 wt% of dried biomass. A. platensis cells were sectionally fractured into small debris after pretreatment. Three-stage fermentation simultaneously promoted H2 yields and overall energy output. Abstract: An integrated process involving cyanobacterium cultivation and three-stage fermentation was investigated to efficiently produce gaseous biofuels. The content and concentration of total carbohydrates in Arthrospira platensis biomass were remarkably enhanced through nutrient adjustments. Relative nitrogen starvation with continuous 15% (v/v) CO2 bubbling led to the accumulation of large-molecular-weight glycogen as an intracellular energy reserve, whereas 0.5 mol/L NaCl addition at 3rd day resulted in the synthesis of small-molecular-weight carbohydrates (e.g., trehalose) as osmoprotectants. The total carbohydrates in A. platen sis cultivated under 15% (v/v) CO2 and 0.5 mol/L NaCl stress occupied 53.4 wt% of the dried biomass. The harvested wet A. platensis biomass was pretreated with dilute acid and steam heating to give the maximum reducing sugar yield of 0.460 g/g volatile solids (VS). Scanning electron microscopy and transmission electron microscopy analyses revealed that the A. platensis cells were fractured section by section and thoroughly disrupted into small debris and fragments after pretreatment. A three-stage process combining dark hydrogen, photo hydrogen, and dark methane fermentation was employed for hydrogen and methane co-production using the pretreated A. platensis biomass. The hydrogen yield was 96 mL/gVS after first-stage dark fermentation, whereas the concentration of soluble metabolic products (SMPs) reached 9.692 g/L. Through the combined dark and photo hydrogen fermentation, the hydrogen yield significantly increased to 429 mL/gVS, corresponding to an SMP removal efficiency of 95.96%. The overall energy yield was boosted to 10.51 kJ/gVS after third-stage dark methane fermentation.